La pobreza en la comunidad indígena de Caimito ( Ucayali) - Díaz Encinas, Alida (2005)
Poverty is presented in the community of Caimito and is manifested through thehigh chronic malnutrition of children smaller than 6 years, low educationallevel, feminine illiteracy, school desertion, low salaries, precarious housing, etc.